A hybrid solid electrolyte Li0.33La0.557TiO3/poly(acylonitrile) membrane infiltrated with a succinonitrile-based electrolyte for solid state lithium-ion batteries. Issue 2 (12th December 2019) - Bi, Jiaying; Mu, Daobin; Wu, Borong; Fu, Jiale; Yang, Hao; Mu, Ge; Zhang, Ling; Wu, Feng
Abstract : An LLTO/PAN/SNE hybrid solid electrolyte membrane with high ionic conductivity and excellent compatibility with both LiFePO4 cathode and metallic lithium anode. Abstract : Solid state lithium-ion batteries are considered as one of the most promising next-generation technologies for energy storage. However, the low ionic conductivity of solid electrolytes and interfacial compatibility issues remain huge challenges to solid state lithium-ion batteries. Herein, a novel hybrid solid electrolyte (HSE) membrane consisting of Li0.33 La0.557 TiO3 (LLTO) ceramic nanorods, poly(acylonitrile) (PAN) and succinonitrile (SN) is constructed. The HSE integrates their merits and shows a high ionic conductivity of 2.20 × 10 −3 S cm −1 at 30 °C. It also exhibits a high electrochemical window of 5.1 V ( vs. Li/Li + ), superior thermal stability and good mechanical properties. When applied in solid state lithium-ion batteries using LiFePO4 as the cathode, the battery demonstrates excellent rate capability and high cycling performance. At a current rate of 0.5C after 150 cycles, the discharge specific capacity still remains at 151 mA h g −1 without decay. This investigation indicates that the HSE membrane could provide a promising solution for high performance solid state lithium-ion batteries.